Efficacy of Complementary Nutritional and Herbal Interventions on Peripheral Inflammatory Biomarkers and Clinical Outcomes in Parkinson’s Disease: A Systematic Review - Putu Ayu Anindita Maheswari Kusumaningtyas Nugraha Budha; Nicky Stevani Wijaya; Marcella Marcella; Alicia Priscila Estelle; Joyceline Chika Tanely (Journal of Asian Medical Students' Association, 2026)
Background: Dopaminergic neuron loss, neuroinflammation, oxidative stress, and disruption of the gut microbiota are all linked to Parkinson's disease, a progressive neurodegenerative condition. Probiotics and synbiotics are examples of non-pharmacological adjuvant treatments that have shown potential advantages through modulation of neurotrophic and inflammatory pathways, while results are still mixed. Purpose of Study: The purpose of this systematic review was to evaluate the impact of non-pharmacological adjuvant therapy on systemic inflammatory biomarkers, neurotrophic factors, metabolic pathways, and clinical outcomes in patients with PD. Methods: Based on PRISMA 2020 guidelines, this study was conducted and the protocol was registered in PROSPERO (CRD420261395485). Literature from PubMed, ProQuest, Science Direct, Springer Nature, and Cochrane Library was screened according to inclusion and exclusion criteria. A total of four RCT were included in the analysis Results: Four randomized controlled trials on probiotics, synbiotics, Zishen Pingchan Granule, and vitamin D3 supplementation in Parkinson's disease were included. The studies showed improvements in inflammatory and neuroprotective biomarkers such TNF-α, IL-6, CRP, BDNF, and α-synuclein, as well as selected motor and non-motor outcomes. No significant treatment-related adverse effects were regularly reported. Principal Conclusion: Complementary nutrition and herbal therapy could provide anti-inflammatory and neuroprotective benefits in Parkinson's disease. However, the current information available is limited by small sample numbers and methodological heterogeneity. Larger standardized trials are needed to confirm the clinical efficacy and long-term therapeutic potential. Keyword: Parkinson’s disease, Placebo, Non-Pharmacological interventions, Inflammatory biomarkers, Neuroprotective biomarkers